Comparative energy metabolism in red and white muscles of juvenile yellowfin tuna, Thunnus albacore - Lu, Zhiyuan; Li, Qian; Yongo, Edwine; Xiao, Juan; Guo, Zhiqiang (Frontiers in Marine Science, 2025)
The musculature of yellowfin tuna (Thunnus albacares) exhibits distinct functional specialization, with slow-twitch oxidative red muscle and fast-twitch glycolytic white muscle demonstrating marked disparities in energy metabolic characteristics. To elucidate the molecular mechanisms underlying these functional divergences, this study implemented an integrated approach incorporating ultrastructural analysis via transmission electron microscopy (TEM), transcriptomic profiling, and enzymatic activity assays of key metabolic regulators. TEM imaging revealed that red muscle fibers contain larger mitochondria and prominent lipid droplets compared to white muscle fibers. Our transcriptome analysis identified 3,162 genes with significant expression differences-1,515 were up-regulated, and 1,647 were down-regulated. Functional enrichment analysis demonstrated significant association of red muscle DEGs with oxidative phosphorylation, tricarboxylic acid cycle, and fatty acid β-oxidation, while white muscle preferentially enriched glycolysis/gluconeogenesis pathways. Enzymatic validation revealed red muscle exhibited higher citrate synthase activity (2.3-fold) and elevated β-hydroxyacyl-CoA dehydrogenase levels (1.8-fold), whereas white muscle showed greater hexokinase activity (4.7-fold) and increased lactate dehydrogenase activity (3.2-fold). These findings provide novel insights into the physiological adaptations underlying the distinctive swimming strategies of scombroid fishes, revealing evolutionary optimization of muscle metabolic pathways corresponding to their sustained cruising capacity and burst swimming performance.